KETAHANAN PANGAN DAN BEBERAPA ASPEKNYA - Adji Sastrosupadi Sastrosupadi (Universitas Tribhuwana Tunggadewi, 2019)
Food self-sufficiency mainly for rice has been known since the old order regime by the implementation of five efforts to agricultural technology, seven, ten and suprainsus ones. In that condition Indonesia has been succeeded in rice self-sufficiency, therefore Indonesia got appreciation from FAO in 1984. In the reformation era, there was a new paradigm namely food security and in President Joko Widodo's regime known as food-sovereignty. In the first step to realized food security and sovereignty, Indonesia has to be able to food self-sufficiency, especially for rice. In that condition Indonesia has been succeeded in rice self-sufficiency in 1984, therefore Indonesia got appreciation from FAO. The main factors affected these paradigms as mentioned above were technical as agricultural technology and now technically ones as socially, economically and behavioral culture of farmer or community. The first factor easily to be solved because so many technologies have been resulted by the research institute, university and private, but the adoption of technology, which has been resulted in the farmer still not yet optimum. The second ones were more difficult to be solved due to the behavior of the farmer or community. Other than three aspects of food, food safety also necessary to be interested, because healthy food has to be free from bacteria and dangerous chemical substances. The success of all paradigms mentioned before not only need cooperation between agriculture and trade departments, but also other sides concern with all paradigms.